2012
DOI: 10.1007/s10194-012-0473-2
|View full text |Cite
|
Sign up to set email alerts
|

An electronic diary on a palm device for headache monitoring: a preliminary experience

Abstract: Patients suffering from headache are usually asked to use charts to allow monitoring of their disease. These diaries, providing they are regularly filled in, become crucial in the diagnosis and management of headache disorders because they provide further information on attack frequency and temporal pattern, drug intake, trigger factors, and short-/long-term responses to treatment. Electronic tools could facilitate diary monitoring and thus the management of headaches. Medication overuse headache (MOH) is a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Acceptability ratings found here are consistent with previous studies, which have reported high participant acceptability ratings of headache diaries . Similar to this study, Allena et al found that e‐diaries were rated as easier to use than paper‐based diaries . Previous research has relied on a handful of non‐theory‐based questions in assessment of participant acceptability of electronic and paper‐based headache measures, and hence there are no comparisons studies available for the current findings on differential group reports on compatibility and intention to use.…”
Section: Resultssupporting
confidence: 90%
“…Acceptability ratings found here are consistent with previous studies, which have reported high participant acceptability ratings of headache diaries . Similar to this study, Allena et al found that e‐diaries were rated as easier to use than paper‐based diaries . Previous research has relied on a handful of non‐theory‐based questions in assessment of participant acceptability of electronic and paper‐based headache measures, and hence there are no comparisons studies available for the current findings on differential group reports on compatibility and intention to use.…”
Section: Resultssupporting
confidence: 90%
“…The extant literature includes nine studies examining patient adherence to a variety of headache diaries, such as paper and pencil diaries, electronic diaries, and online digital assistant (ODA) self‐monitoring. Documented adherence rates to paper headache diaries for patients with headache and migraine are 83.3% and 95%, while adherence rates to electronic headache diaries are 90% in patients with migraine and 98% in patients receiving inpatient treatment for medication overuse headache . Allena and colleagues also investigated the relationship between demographic and disease variables with electronic headache diary adherence and found differences in diary adherence based on age, education, or baseline headache disability .…”
Section: Resultsmentioning
confidence: 99%
“…Documented adherence rates to paper headache diaries for patients with headache and migraine are 83.3% and 95%, while adherence rates to electronic headache diaries are 90% in patients with migraine and 98% in patients receiving inpatient treatment for medication overuse headache . Allena and colleagues also investigated the relationship between demographic and disease variables with electronic headache diary adherence and found differences in diary adherence based on age, education, or baseline headache disability . Tassorelli and colleagues provided data for varying levels of diary completion which demonstrated that 71% of patients with headache and migraine returned a “completed” diary, 28% returned an “almost” completed diary, and 1% returned a “fairly” completed diary .…”
Section: Resultsmentioning
confidence: 99%
“…More than half of this burden in disability-adjusted life years (DALYs) is contributed by cerebrovascular disease, Alzheimer and other dementias, epilepsy, and migraines. EMR have been shown to be useful in the management of these diseases 4,5 as they promote better coordination within the health care system.…”
mentioning
confidence: 99%